2014
DOI: 10.1136/bcr-2014-206214
|View full text |Cite
|
Sign up to set email alerts
|

Unprovoked deep venous thrombosis in a young adult associated with membranous obstruction of inferior vena cava

Abstract: Unprovoked deep venous thrombosis (DVT) in young adults is an unusual phenomenon, but it is associated with significant morbidity. Developmental anomalies of the inferior vena cava (IVC) should be considered as a possible aetiological factor, and appropriate investigations should be performed to determine the conclusive diagnosis and necessary treatment plan. We report a case of spontaneous thrombosis of the IVC and bilateral iliac venous system in a young man, associated with membranous obstruction of the IVC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…While the incidence of DVT in young adults is rare [39], the development of DVT at a younger age is related to thrombophilic disorders and anomalies of the inferior vena cava (IVC) [40]. IVC anomalies could affect the blood return of the lower extremities and increase the condition of venous stasis and venous hypertension [41], while thrombophilia is a hypercoagulation state due to the over-activity of coagulation factors. However, the higher correlation between younger DVT patients and sepsis compared with older DVT patients may be due to the different distribution of co-infection between the age subgroups, and more studies are required for a plausible mechanism and confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…While the incidence of DVT in young adults is rare [39], the development of DVT at a younger age is related to thrombophilic disorders and anomalies of the inferior vena cava (IVC) [40]. IVC anomalies could affect the blood return of the lower extremities and increase the condition of venous stasis and venous hypertension [41], while thrombophilia is a hypercoagulation state due to the over-activity of coagulation factors. However, the higher correlation between younger DVT patients and sepsis compared with older DVT patients may be due to the different distribution of co-infection between the age subgroups, and more studies are required for a plausible mechanism and confirmation.…”
Section: Discussionmentioning
confidence: 99%
“…Although 1 study suggested that thrombotic episodes in young adults are comparatively rare, and more risk factors are required to precipitate thrombosis at a younger age, 36 alterations in the thrombophilia profile were found to be prominent risk factors for VTE at a young age. 37,38 However, none of these studies were from HA regions. The present study suggested various altered hemostasis variables at HA as plausible risk factors for VTE episodes at a young age, thereby exclusively associating VTE incidence at altitude with age during the event.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed the age distribution: 81.13% of the HAP population was #40 years of age, whereas only 62.22% of SLPs fell into this range. The median (IQR) age of 33 (29)(30)(31)(32)(33)(34)(35)(36)(37)(38) years in HAPs was significantly lower than in their corresponding SLPs, which was 36 (31-43.5) years ( Figure 1A). Likewise, patients with CVT, DVT, and PVT from HA were comparatively younger than their manifestation type-matched SLP counterparts ( Figure 1B).…”
Section: Characteristics Of the Study Populationmentioning
confidence: 99%